Towards the Essence of Andragogy – A Hermeneutical Reading of Grundtvig, Knowles, Lindeman and Savićević - Malinen, Anita; Piirainen, Arja (AS. Andragoška spoznanja, 2023)
The aim of this study is to search for the essence of andragogy through a critical examination of andragogy theorists and thereby increase the theoretical understanding of andragogy. Systematic reviews in 2013 and in 2021 led us to probe more deeply into andragogical writings in search of the essence of andragogy. Writings by four classic theorists representing different andragogical approaches – Grundtvig, Knowles, Lindeman and Savićević – were selected for hermeneutic text interpretation. Based on the results, we formulated, as constituting the essence of andragogy, three intertwined principles: 1) lived experience, 2) reciprocal interaction, and 3) “power with”. Each principle expresses the qualities that describe its nature. These three principles are necessary and sufficient conditions for the andragogy to be present. If one of these principles is lacking, the wholeness of andragogy is absent, and the phenomenon does not exist. Namen prispevka je iskanje bistva andragogike prek kritičnega preučevanja del teoretikov andragogike in poglobljenega teoretičnega razumevanja področja. Sistematična pregleda iz let 2013 in 2021 sta nas v iskanju bistva andragogike spodbudila k bolj poglobljenemu branju andragoških del. Za hermenevtično branje in interpretacijo so bila izbrana besedila štirih klasičnih teoretikov Grundtviga, Knowlesa, Lindemana in Savićevića, ki predstavljajo različne andragoške pristope. Na podlagi rezultatov smo oblikovali tri med seboj prepletena načela, ki predstavljajo bistvo andragogike: 1) življenjska izkušnja, 2) vzajemna interakcija in 3) »moč z« (ang. power with). Vsako od načel izraža lastnosti, ki opisujejo njegovo naravo. Ta tri načela so nujni in zadostni pogoji, da lahko govorimo o andragogiki. Če manjka eno od načel, ne gre za andragogiko, fenomen ne obstaja.